1. The problem statement, all variables and given/known data Simplify the following boolean expression: A'C + A'C'D + ABC + ABC'D I have a solution but when I checked against a boolean algebra simplifier online it gave me a different answer... is there a glaring mistake below ? 2. Relevant equations None. 3. The attempt at a solution A'C + A'C'D + ABC + ABC'D = A'(C + C'D) + AB(C + C'D) = A'(C + D) + AB(C + D) = A'C + A'D + ABC + ABD = C(A' + AB) + D(A' + AB) = C(A'B + 1) + D(A'B + 1) = C(1) + D(1) = C + D. Any help would be much appreciated !